2008
DOI: 10.1002/jor.20565
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone modulates BMP‐2 effects on mesenchymal stem cells in vitro

Abstract: Dexamethasone/ascorbic acid/glycerolphosphate (DAG) and bone morphogenic protein (BMP)-2 are potent agents in cell proliferation and differentiation pathways. This study investigates the in vitro interactions between dexamethasone and BMP-2 for an osteoblastic differentiation of mesenchymal stem cells (MSCs). Bone marrow-derived human MSCs were cultured with DAG (group A), BMP-2 þ DAG (group B), and DAG þ BMP-2 combined with a porous collagen I/III scaffold (group C). RT-PCR, ELISA, immuncytochemical stainings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 63 publications
3
55
0
Order By: Relevance
“…However, it is unlikely that these factors include chemicals such as ascorbic acid, dexamethasone and β-glycerol phosphate, which are the key constituents of osteogenic media, as the authors are unaware of any evidence that osteocytes or osteoblasts are capable of secreting such chemicals. It is likely that the are targeting similar proteins to the osteogenic medium additives which are responsible for producing the collagen, BMPs and phosphate secretion required for bone formation (Jäger et al, 2008).…”
Section: Discussion With Reviewersmentioning
confidence: 99%
“…However, it is unlikely that these factors include chemicals such as ascorbic acid, dexamethasone and β-glycerol phosphate, which are the key constituents of osteogenic media, as the authors are unaware of any evidence that osteocytes or osteoblasts are capable of secreting such chemicals. It is likely that the are targeting similar proteins to the osteogenic medium additives which are responsible for producing the collagen, BMPs and phosphate secretion required for bone formation (Jäger et al, 2008).…”
Section: Discussion With Reviewersmentioning
confidence: 99%
“…The amounts of BMP-2 applied did not appear to enhance implant-osseointegration in large buccal defects. Jäger et al 26) reported that BMP-2 enhances osteogenic differentiation of mesenchymal bone marrow cells in vitro within medium containing dexamethasone, ascorbic acid, and -glycerophosphate. BMP-2 was contained in the osteogenic differentiation culture medium in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect of dexamethasone on osteogenic differentiation of bone marrow MSCs has been extensively studied for several decades [17][18][19][20][21], the synergistic effect between dexamethasone and BMPs was recently examined. Jäger et al reported that BMP-2 enhanced ODM-induced osteogenic differentiation in human mesenchymal bone marrow cells [22]. A later study conducted in rat dental follicle progenitor cells showed that the joint application of dexamethasone and BMP-2 achieved the highest ALP activity, calcium and phosphonium and osteocalcin content compared with the groups treated with dexamethasone or BMP-2 alone [23].…”
Section: Discussionmentioning
confidence: 99%